2016
DOI: 10.1097/mca.0000000000000412
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous coronary artery dissection

Abstract: Spontaneous coronary artery dissection (SCAD) remains an infrequent, elusive, and challenging clinical entity of unknown etiology eight decades after its initial description. Our understanding of the pathophysiology of SCAD, initially limited to information from early pathological studies, case reports, and very short series, has been enriched recently by relatively large contemporary series of patients studied prospectively. The typical presentation involves a young woman without coronary risk factors sufferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 63 publications
0
35
1
1
Order By: Relevance
“…These findings are at variance with previous reports of spontaneous healing in most nonpregnant patients with SCAD 103,117,127,128 and emphasize the difference in the natural history of this disease when associated with pregnancy.…”
Section: Follow-upcontrasting
confidence: 57%
“…These findings are at variance with previous reports of spontaneous healing in most nonpregnant patients with SCAD 103,117,127,128 and emphasize the difference in the natural history of this disease when associated with pregnancy.…”
Section: Follow-upcontrasting
confidence: 57%
“…Tweet et al reported an annual incidence of SCAD of 0.26 per 100,000 persons [6]. However, the true incidence of SCAD may be underestimated for three reasons: (1) initial presentation as sudden death, (2) underuse or avoidance of coronary angiography in young women, and (3) under-recognition of angiographic characteristics of the disease [4,6].…”
Section: Discussionmentioning
confidence: 99%
“…Angiographically or on autopsy, SCAD was reported in 27-43% of patients, whereas atherosclerotic plaque was observed in 27-40% [3,5]. SCAD is a rare condition with a prevalence of 0.1-1.1% on angiography [4]. Tweet et al reported an annual incidence of SCAD of 0.26 per 100,000 persons [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous coronary artery dissection (SCAD) is a rare, poorly understood disease (incidence 0.1-1.1%) [1]. Some large studies have been done to give more clarity on this disease, hence some controversy exists as to previous generally accepted ideas.…”
Section: Introductionmentioning
confidence: 99%